Peningkatan Pendapatan dengan Rebranding logo dan Kemasan untuk Galih’s Snack - Anam, saiful; halik, abdul; pramesthi, gita winandha; sembada, Yoga septian alea; Selvia, Dila; nurhadi, muizzu (JUDIKAT: Jurnal Pengabdian Kepada Masyarakat, 2025)
Wonorejo sub-district has the potential for MSMEs that should be developed, but public awareness of the development of MSMEs is still low. This is indicated by business actors who are not good at product packaging which affects their sales. Therefore, it is necessary to build an identity by creating a logo that will be displayed on the product packaging to strengthen marketing in a wider reach. In addition, the creation of legality is very necessary in the MSME partner identity building program that we will develop. With the synergy between building brand identity through a strong logo, attractive and functional packaging design, and fulfilling business legality, it is hoped that partner kebab chip products can build a professional and trusted image. Increasing brand visibility in the market, higher consumer trust, and access to wider distribution channels will significantly strengthen the marketing position of partner products. Ultimately, this comprehensive strategy aims to support the sustainability and growth of MSMEs, so that they can contribute more to the local and national economy, and compete effectively in an increasingly dynamic market. This holistic approach is expected to be a model for other MSMEs who want to increase the competitiveness of their products through the development of a structured brand identity and compliance with market regulations Keywords: Brand identity, Kebab chips.